Hate Speech Discourse in Rector Election Messages in Digital Space - Suhartini, Lelly; Udu, Hamiruddin; Hidrawati (Institut Agama Islam Negeri (IAIN) Kendari, 2025)
Despite the growing body of hate speech studies in Indonesia, existing research has predominantly concentrated on ethnic and religious domains, leaving its construction within institutional political arenas, such as university rector elections, largely underexplored. Addressing this gap, the present study examines how hate speech is discursively constructed in media coverage of the Rector Election at one University in Southeast Sulawesi, Indonesia, drawing on reports published by FramingNewsTV.com and other national news outlets. Grounded in an integrative theoretical framework that combines Sociolinguistics with Norman Fairclough’s Critical Discourse Analysis (CDA), this qualitative study analyzes hate speech across three analytical dimensions: textual features, discursive practices, and social practices. The findings demonstrate that hate speech in this context is predominantly constructed in covert forms. At the textual level, it operates through three main strategies: the use of sensational and negatively charged vocabulary, the deployment of war and theatrical metaphors, and the dramatization of legal registers to produce a “truth effect.” At the level of discursive practice, these strategies function to construct rigid in-group and out-group identities, intensifying polarization and constraining substantive public dialogue. At the level of social practice, hate speech emerges as an instrument of epistemic struggle, aimed at delegitimizing formal authorities and undermining symbolic power and individual agency. Theoretically, this study proposes the Critical Digital Sociolinguistics model as a contextualized framework for analyzing hate speech in digital political discourse in Indonesia. Practically, the findings highlight the need for enhanced media literacy and more nuanced regulatory guidelines capable of detecting covert and systemic forms of hate speech beyond explicit expressions